2016
DOI: 10.1038/srep26633
|View full text |Cite
|
Sign up to set email alerts
|

Selective serotonin 5-HT1A receptor biased agonists elicitdistinct brain activation patterns: a pharmacoMRI study

Abstract: Serotonin 1A (5-HT1A) receptors are involved in several physiological and pathological processes and constitute therefore an important therapeutic target. The recent pharmacological concept of biased agonism asserts that highly selective agonists can preferentially direct receptor signaling to specific intracellular responses, opening the possibility of drugs targeting a receptor subtype in specific brain regions. The present study brings additional support to this concept thanks to functional magnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 54 publications
5
32
0
1
Order By: Relevance
“…Thus, F13714 potently inhibits 5-HT release in cortex and striatum (Assié et al, 2006; Iderberg et al, 2015), reverses L-DOPA-induced dyskinesia in Parkinsonian rats, and stimulates a BOLD signal in the raphe, striatum, and motor cortex (Becker et al, 2016), results that are consistent with the present study showing accentuated binding to these brain regions in marmoset brain. Although the molecular basis for this remains to be clarified, it is likely due to a preferential interaction of 18 F-F13714 with 5-HT 1A receptors that are coupled to specific G-protein subtypes and/or intracellular signaling mechanisms (Newman-Tancredi, 2011).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Thus, F13714 potently inhibits 5-HT release in cortex and striatum (Assié et al, 2006; Iderberg et al, 2015), reverses L-DOPA-induced dyskinesia in Parkinsonian rats, and stimulates a BOLD signal in the raphe, striatum, and motor cortex (Becker et al, 2016), results that are consistent with the present study showing accentuated binding to these brain regions in marmoset brain. Although the molecular basis for this remains to be clarified, it is likely due to a preferential interaction of 18 F-F13714 with 5-HT 1A receptors that are coupled to specific G-protein subtypes and/or intracellular signaling mechanisms (Newman-Tancredi, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…These considerations suggest that differences in labeling patterns between the 2 tracers may relate to the agonist properties of 18 F-F13714 that enable it to distinguish a 5-HT 1A receptor subpopulation of high-affinity sites (Assié et al, 2006; Maurel et al, 2007; Lemoine et al, 2012), a concept described previously for the 5-HT 1A receptor in baboons with 11 C-CUMI-101 (agonist) and 11 C-WAY100635 (antagonist) (Kumar et al, 2012). In the case of F13714, extensive evidence supports the notion that it acts as a biased agonist that preferentially targets 5-HT 1A receptors in specific brain regions, including the raphe, striatum, and thalamus (Assié et al, 2006; Iderberg et al, 2015; Becker et al, 2016). …”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…W testach funkcjonalnych in vitro związek F15599 wykazywał wyraźną preferencję (ok. 30 razy) wobec aktywacji fosforylacji kinazy ERK względem inhibicji cyklazy adenylanowej. Wykorzystując badania elektrofizjologiczne, mikrodializę i neuroobrazowanie, stwierdzono, że oddziałuje on preferencyjnie na postsynaptyczne receptory 5-HT 1A , szczególnie te zlokalizowane w korze mózgowej [67,68]. W konsekwencji odznacza się wysoką aktywnością w zwierzęcych modelach zaburzeń nastroju (test wymuszonego pływania, wokalizacja ultradźwiękowa) [69] oraz odwraca deficyty funkcji poznawczych u szczurów wywołane substancją psychozomimetyczną -fencyklidyną [70].…”
Section: Agoniści Receptora 5-ht 1a Wykazujący Selektywność Funkcjonaunclassified
“…30x) for activation of phosphorylation of ERK with respect to inhibition of adenylate cyclase. Using electrophysiological studies, microdialysis and neuroimaging, it has been found that it acts preferentially on postsynaptic 5-HT 1A receptors, especially those located in the cerebral cortex [67,68]. As a result, it displays high activity in animal models of mood disorders (forced swimming test, ultrasonic vocalisation) [69], and reverses cognitive function deficits in rats induced by a psychotomimetic substance -phencyclidine [70].…”
Section: -Ht 1a Receptor Agonists Displaying Functional and Regionalmentioning
confidence: 99%